Drugs: America's holy war - Benavie, Arthur (Routledge, 2009)
Background -- Overview -- The birth of the drug war -- Damage from the drug war -- Crime -- Public health -- Civil liberties -- Social cohesion -- Your tax dollars at work -- The federal government's case for the drug war -- The perception of the drug czars -- The czars defend the drug war -- The White House versus the scientists on marijuana dangers -- Czars versus the scientists on cocaine and heroin -- Beyond the drug war -- Harm reduction instead of war -- Legalizing marijuana -- Reforming the laws on hard drugs -- Questions and answers